(untitled) (Estudios Sociales, 2021)
Studies on the relationship between labour and politics in Argentina during the oligarchic regime tend to focus on the political initiatives of Socialists and Anarchists militants. In order to present a more complete picture of the political experience of Buenos Aires’s working classes, this article draws attention to Catholics, Liberals and factory owners – whose importance has been largely neglected in historical accounts of the world of labour in this period. Finally, it also looks at the links between unions and left wing activists and the State.